Thickener for cyanoacrylate adhesives, method for producing the same, and method for producing cyanoacrylate adhesives

JP2025026302APending Publication Date: 2025-02-21ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024081247
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-05-17
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0022】 本発明によれば、シアノアクリレート系接着剤用増粘剤として利用した時に、保管中のシアノアクリレート系接着剤の粘度変化を抑制出来る増粘剤を提供することができる。 また、本発明の一つの態様では、上記化合物を粉体にすることで、接着剤の保管安定性を更に改善することが出来る。更に、本発明の一つの態様では、この増粘剤を特定の包装状態のパッケージ体とすることで、接着剤の保管安定性を更に改善することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026302000001_ABST
    Figure 2025026302000001_ABST
Patent Text Reader

Abstract

To provide a thickener that exhibits little change in viscosity when used as a thickener for cyanoacrylate adhesives.SOLUTION: A thickener for cyanoacrylate adhesives comprises: a methacrylic resin in a bead form with an average particle diameter of 50 to 500 μm and a moisture content of 1 mass% or less; and a compound represented by the general formula (1) in the figure. The content of the compound represented by the general formula (1) is 0.01 mass% to 10 mass% relative to 100 mass% of the methacrylic resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thickener for cyanoacrylate adhesives and a method for producing the same, as well as a method for producing a cyanoacrylate adhesive. [Background technology]

[0002] In the manufacture of paints or adhesives, thickeners are used to adjust the viscosity of the product and improve its handling. Among the thickeners, those using methacrylic resin compositions have high transparency and weather resistance as transparent resins, and also have excellent affinity with adhesives such as alkyl cyanoacrylates and chemical resistance. Methacrylic resin compositions are widely used as thickeners for adhesives because they dissolve quickly in monomers while maintaining transparency.

[0003] Among adhesives, cyanoacrylate adhesives in particular have a high anionic polymerization property of the main component, alkyl cyanoacrylate, which initiates polymerization with a small amount of moisture or weak anions such as impurities, and can firmly bond various materials in a short time. Therefore, they are used as instant adhesives in a wide range of fields such as industrial, medical, and household applications.

[0004] Furthermore, because cyanoacrylate adhesives have a high degree of polymerizability, an anionic polymerization inhibitor or a radical polymerization inhibitor is used in order to stabilize the viscosity.

[0005] However, cyanoacrylate adhesives that have been given viscosity by dissolving methacrylic resins have the problem that they are unable to exhibit the expected polymerization inhibition ability due to the anionic polymerization promoters and radical polymerization promoters present in the methacrylic resins, and their viscosity increases during storage.

[0006] For example, Patent Document 1 discloses a cyanoacrylate adhesive containing various polymerization inhibitors.

[0007] For example, Patent Document 2 discloses a thickener containing a methacrylic resin that has excellent storage stability when exposed to 50° C. / 95% Rh in methyl methacrylate.

[0008] For example, Patent Document 3 describes that a cyanoacrylate adhesive composition contains a polyalkyl(meth)acrylate having a weight average molecular weight of 200,000 or more as a thickening agent. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 3018859 [Patent Document 2] JP 2018-178076 A [Patent Document 3] Special Publication No. 4-15267 Summary of the Invention [Problem to be solved by the invention]

[0010] However, Patent Document 1 does not describe the effect of the thickener on polymerization.

[0011] In addition, Patent Document 2 provides a thickener with excellent long-term stability in methyl methacrylate by introducing a specific structure into the end of the resin, but does not disclose viscosity stability in alkyl cyanoacrylate.

[0012] Furthermore, in Patent Document 3, the cyanoacrylate adhesive is prepared by adding various stabilizers, and there is no description of the effect of a thickener on polymerization.

[0013] Therefore, an object of the present invention is to provide a thickener for cyanoacrylate adhesives that can be suitably used as a thickener for adhesives, and in particular, when used as a thickener for cyanoacrylate adhesives, exhibits little viscosity change due to polymerization and has excellent storage stability. Another object of the present invention is to provide a method for producing such a thickener for cyanoacrylate adhesives, and a method for producing an adhesive containing such a thickener for cyanoacrylate adhesives. [Means for solving the problem]

[0014] To solve the above problems, the inventors conducted extensive research and surprisingly discovered that a thickener for cyanoacrylate adhesives, which is in the form of beads having an average particle size of 50 to 500 μm and contains a methacrylic resin with a moisture content of 1 mass % or less and a compound represented by the following general formula (1), and the compound represented by the following general formula (1) is contained in an amount of 0.01 mass % to 10 mass % relative to 100 mass % of the methacrylic resin, can suppress changes in viscosity of the cyanoacrylate adhesive during storage. [ka] [In general formula (1), R1 represents a hydrogen atom, a methyl group, or a tertiary butyl group, and R2 and R3 each independently represent a hydrogen atom, a methyl group, a tertiary butyl group, a hydroxyl group, or a methoxy group, provided that the total number of tertiary butyl groups in R1, R2, and R3 is less than 2.]

[0015] That is, the present invention is as follows. [1] A bead-shaped polymer having an average particle size of 50 to 500 μm, comprising a methacrylic resin having a moisture content of 1 mass% or less and a compound represented by the above general formula (1), A thickener for cyanoacrylate adhesives, comprising 0.01% by mass to 10% by mass of the compound represented by the general formula (1) relative to 100% by mass of a methacrylic resin.

[0016] [2] The thickener for cyanoacrylate adhesives according to [1], wherein the weight average molecular weight of the methacrylic resin is 85,000 or more and 5,000,000 or less.

[0017] [3] The thickener for cyanoacrylate adhesives according to [1] or [2], wherein the compound represented by the general formula (1) is in the form of powder at room temperature.

[0018] [4] The thickener for cyanoacrylate adhesives according to any one of [1] to [3], wherein the compound represented by the general formula (1) contains two hydroxyl groups or one hydroxyl group and one methoxy group.

[0019] [5] A method for producing the cyanoacrylate adhesive thickener according to any one of [1] to [4], comprising the steps of: A drying step of volatilizing water from the methacrylic resin; A method for producing a cyanoacrylate adhesive thickener, comprising at least a packaging step of packaging the methacrylic resin and the compound represented by general formula (1) in a packaging material after the drying step.

[0020] [6] The thickener for cyanoacrylate adhesives according to any one of [1] to [4] is used in a composition having a water vapor permeability of 1.0 g / (m 2 - The package is sealed in packaging material for less than 24 hours.

[0021] [7] A method for producing a cyanoacrylate adhesive, comprising contacting a bead-shaped methacrylic resin having an average particle size of 50 to 500 μm and a moisture content of 1 mass% or less with a compound represented by the above general formula (1) in an amount of 0.01 mass% to 10 mass% relative to 100 mass% of the methacrylic resin, and then dissolving the compound in a cyanoacrylate adhesive. Effect of the Invention

[0022] According to the present invention, it is possible to provide a thickener that, when used as a thickener for a cyanoacrylate adhesive, can suppress changes in viscosity of the cyanoacrylate adhesive during storage. In one embodiment of the present invention, the storage stability of the adhesive can be further improved by making the compound into a powder. In another embodiment of the present invention, the thickener can be packaged in a specific packaging state to further improve the storage stability of the adhesive. [Brief description of the drawings]

[0023] [Figure 1] 5A to 5C are schematic diagrams illustrating an example of a method for producing an adhesive according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described in detail. The present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention.

[0025] [Thickener] The thickener for cyanoacrylate adhesives of the present embodiment (hereinafter, sometimes simply referred to as "thickener") has the following properties: A bead-shaped methacrylic resin having an average particle size of 50 to 500 μm and a moisture content of 1% by mass or less; A compound represented by the following general formula (1): The compound represented by the general formula (1) is contained in an amount of 0.01% by mass to 10% by mass relative to 100% by mass of a methacrylic resin, which is a thickener for cyanoacrylate adhesives. [ka] [In general formula (1), R1 represents a hydrogen atom, a methyl group, or a tertiary butyl group, and R2 and R3 each independently represent a hydrogen atom, a methyl group, a tertiary butyl group, a hydroxyl group, or a methoxy group, provided that the total number of tertiary butyl groups in R1, R2, and R3 is less than 2.] When used as a thickener for cyanoacrylate adhesives, the thickener for cyanoacrylate adhesives can suppress changes in viscosity of the cyanoacrylate adhesives during storage.

[0026] The thickener of the present embodiment contains at least a methacrylic resin. The thickener may contain only a methacrylic resin as a resin component, or may contain a methacrylic resin and other resins. The thickener preferably contains 90% by mass or more of a methacrylic resin as a resin component. The thickener preferably contains only a methacrylic resin as a resin component. The thickener may contain one type of methacrylic resin alone or two or more types of methacrylic resin in combination. In one example, it is more preferable that the thickener contains only a single methacrylic resin as a resin component.

[0027] The thickener of the present embodiment contains a compound represented by the above general formula (1). The thickener contains the compound represented by the above general formula (1) in an amount of 0.01% by mass to 10% by mass relative to 100% by mass of the methacrylic resin. The thickener contains the compound represented by the above general formula (1) in an amount of 0.03% by mass or more from the viewpoint of suppressing viscosity change in the thickener. Other preferred ranges of the content of the compound represented by the above general formula (1) are 0.05% by mass or more, and more preferably 0.08% by mass or more. In addition, the thickener contains the compound represented by the above general formula (1) in an amount of 8% by mass or less from the viewpoint of suppressing coloring due to addition. Other preferred ranges of the content of the compound represented by the above general formula (1) are 5% by mass or less, 3% by mass or less, and more preferably 2% by mass or less. In addition, the compound represented by the above general formula (1) may be used alone or in combination of two or more kinds.

[0028] The thickener of the present embodiment can be suitably used as a thickener for cyanoacrylate adhesives. In addition, since the adhesive mechanism of cyanoacrylate adhesives is anionic polymerization with moisture, it is believed that the compound represented by the above general formula (1), which has the ability to inhibit radical polymerization, does not affect the original adhesive ability, regardless of the above range of parts or type.

[0029] [Methacrylic resin] In this embodiment, the methacrylic resin preferably has a weight average molecular weight (Mw) of 85,000 or more and 5,000,000 or less. The weight average molecular weight (Mw) of the methacrylic resin is more preferably 300,000 or more and 5,000,000 or less, because a desired viscosity can be obtained by adding a small amount, and is more preferably 300,000 or more and 4,000,000 or less, because if the amount added is too small, it is affected by variations in weighing.

[0030] The methacrylic resin is in the form of beads having an average particle size of 50 to 500 μm. From the viewpoint of solubility in a cyanoacrylate adhesive, the average particle size of the methacrylic resin is more preferably 50 to 350 μm.

[0031] The moisture content of the methacrylic resin is 1% by mass or less, and preferably 0.01% by mass or more and 1% by mass or less. When trying to keep the moisture content of the methacrylic resin lower, it may be necessary to dry it for a long time. Therefore, from the viewpoint of productivity, the moisture content of the methacrylic resin is preferably 0.01% by mass or more. On the other hand, if the moisture content of the methacrylic resin exceeds 1% by mass, the storage stability after dissolving in cyanoacrylate such as ethyl cyanoacrylate tends to deteriorate due to the influence of promoting anionic polymerization, so the moisture content of the methacrylic resin is preferably 1% by mass or less. The moisture content of the methacrylic resin is more preferably 0.01% by mass or more and 0.8% by mass or less, even more preferably 0.02% by mass or more and 0.7% by mass or less, and most preferably more than 0.03% by mass and less than 0.5% by mass.

[0032] In this embodiment, unless otherwise specified, the methacrylic resin preferably contains 80% by mass or more of methyl methacrylate monomer units as monomer units. The methacrylic resin may also contain alkyl acrylate monomer units as monomer units. From the viewpoint of odor suppression when dissolved in a certain substance (for example, when dissolved in alkyl cyanoacrylate), the methacrylic resin preferably contains 90 to 99.9% by mass of methyl methacrylate monomer units and 0.1 to 10% by mass of alkyl acrylate monomer units. The methacrylic resin more preferably contains 95 to 99.8% by mass of methyl methacrylate monomer units, further preferably contains 97 to 99.8% by mass, and particularly preferably contains 98 to 99.8% by mass of methyl methacrylate monomer units. The methacrylic resin may or may not contain other monomer units other than the methyl methacrylate monomer units and the alkyl acrylate monomer units. The above-mentioned methacrylic resin not only reduces the change in viscosity, but also suppresses odor when dissolved in a substance such as alkyl cyanoacrylate.

[0033] In this embodiment, the mass ratio of the alkyl acrylate monomer unit to 100% by mass of the methacrylic resin is preferably 0.1 to 10% by mass. The mass ratio of the alkyl acrylate monomer unit to 100% by mass of the methacrylic resin is more preferably 0.2 to 5% by mass, even more preferably 0.2 to 3% by mass, and particularly preferably 0.2 to 2% by mass. When the mass ratio of the alkyl acrylate monomer unit to 100% by mass of the methacrylic resin is 10% by mass or less, it is preferable because when the methacrylic resin is dissolved in an alkyl cyanoacrylate or the like, a peculiar odor due to the remaining alkyl acrylate monomer or impurities derived therefrom is not generated. On the other hand, when the mass ratio of the alkyl acrylate monomer unit to 100% by mass of the methacrylic resin is 0.1% by mass or more, it is preferable because it is possible to exert an effect of improving the odor obtained by copolymerizing the alkyl acrylate monomer unit.

[0034] The alkyl acrylate monomer unit preferably has an alkyl group having 4 or more carbon atoms. As the alkyl acrylate monomer unit having an alkyl group having 4 or more carbon atoms, a monomer unit derived from an alkyl acrylate having an alkyl group having 4 to 8 carbon atoms, such as n-butyl acrylate, sec-butyl acrylate, or 2-ethylhexyl acrylate, is preferably used. From the viewpoint of reducing the odor of a cyanoacrylate solution of a methacrylic resin, the alkyl group of the alkyl acrylate monomer unit preferably has 4 to 8 carbon atoms. In addition, from the viewpoint of easy availability and reducing the odor when dissolved in cyanoacrylate, the alkyl acrylate monomer unit is particularly preferably an n-butyl acrylate monomer unit.

[0035] The methacrylic resin may be composed only of methyl methacrylate monomer units and alkyl acrylate monomer units having an alkyl group having 4 or more carbon atoms, or may further contain other monomer units.

[0036] The other monomer units may be vinyl monomer units copolymerizable with methyl methacrylate, and specific examples thereof include alkyl methacrylates having an alkyl group with 2 to 18 carbon atoms; alkyl acrylates having an alkyl group with 1 to 3 carbon atoms; α,β-unsaturated acids such as acrylic acid and methacrylic acid; acrylic acid esters containing an aromatic group such as benzyl acrylate; unsaturated group-containing divalent carboxylic acids and their alkyl esters such as maleic acid, fumaric acid, and itaconic acid; aromatic vinyl compounds such as styrene, α-methylstyrene, and styrene having a substituent on the benzene ring; cyanide vinyl compounds such as acrylonitrile and methacrylonitrile; maleic anhydride, maleimide, N Examples of the ester include substituted maleimides, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and other ethylene glycol or oligomers thereof, in which both terminal hydroxyl groups are esterified with acrylic acid or methacrylic acid, neopentyl glycol di(meth)acrylate, and other two alcohol hydroxyl groups are esterified with acrylic acid or methacrylic acid, trimethylolpropane, pentaerythritol, and other polyhydric alcohol derivatives are esterified with acrylic acid or methacrylic acid, and polyfunctional monomers such as divinylbenzene. These may be used alone or in combination of two or more. From the viewpoint of odor suppression, when an alkyl acrylate having an alkyl group with 1 to 3 carbon atoms is contained, the mass ratio of monomer units derived from an alkyl acrylate having an alkyl group with 1 to 3 carbon atoms is preferably less than 0.1 mass% relative to 100 mass% of all monomer units constituting the methacrylic resin, and more preferably 0 mass%, i.e., no monomer units derived from an alkyl acrylate having an alkyl group with 1 to 3 carbon atoms are contained.

[0037] In this embodiment, other monomer units may be copolymerized within a range that does not impair the effects of the present invention. Considering the solubility in cyanoacrylate and the like, the odor during dissolution, and the like, when the total amount of methyl methacrylate and alkyl acrylate monomer units having an alkyl group with 4 or more carbon atoms is taken as 100 parts by mass, the mass ratio of monomer units derived from other vinyl monomers copolymerizable with methyl methacrylate is preferably 0 to 20 parts by mass, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less in 100 parts by mass of the methacrylic resin.

[0038] In 100 parts by mass of the methacrylic resin, the total mass proportion of the monomer units derived from methyl methacrylate and the alkyl acrylate monomer units having an alkyl group having 4 or more carbon atoms is preferably 80 parts by mass or more, more preferably 85 parts by mass or more, even more preferably 90 parts by mass or more, even more preferably 95 parts by mass or more, and particularly preferably 100 parts by mass.

[0039] [Compound represented by general formula (1)] As described above, the thickener of the present embodiment contains a compound represented by the following general formula (1). [ka] In this embodiment, in the above general formula (1), R1 represents a hydrogen atom, a methyl group, or a tertiary butyl group, and R2 and R3 each independently represent a hydrogen atom, a methyl group, a tertiary butyl group, a hydroxyl group, or a methoxy group, provided that the total number of tertiary butyl groups in R1, R2, and R3 is less than two. In terms of the effect of suppressing viscosity change, the general formula (1) more preferably contains two hydroxyl groups, or one hydroxyl group and one methoxy group.

[0040] The form of the compound represented by the above general formula (1) is not particularly specified, but it is preferable that it is a solid at room temperature in terms of handling. A more preferable form of the compound represented by the above general formula (1) is a powder at room temperature in order to stably suppress the viscosity change when dissolved in a cyanoacrylate adhesive in terms of uniform mixing with the methacrylic resin in the package. When the compound represented by the above general formula (1) is in the form of a powder, it is possible to increase the contact area by uniform mixing, and it has the effect of suppressing the radical state and polymerization reaction of the methacrylic resin in the package.

[0041] The method for adding the compound represented by general formula (1) to the methacrylic resin is not limited, but in order to suppress anionic polymerization of the cyanoacrylate adhesive, it is preferable to add the compound represented by general formula (1) after a drying process in which the water content of the methacrylic resin is volatilized.

[0042] In the manufacturing method of the cyanoacrylate adhesive thickener of this embodiment, it is preferable to include a packaging step of packaging the methacrylic resin and the compound represented by general formula (1) in a packaging material. In addition, in the manufacturing method of the cyanoacrylate adhesive thickener of this embodiment, it is preferable to include a drying step of volatilizing the moisture of the methacrylic resin before the packaging step. From the viewpoint of reducing viscosity change, it is not a problem if the methacrylic resin and the compound represented by general formula (1) are in contact with each other even if they are not in the same package. That is, only the methacrylic resin may be packaged in a packaging material, and then the methacrylic resin and the compound represented by general formula (1) may be brought into contact with each other.

[0043] When the methacrylic resin and the compound represented by general formula (1) are packaged together, the packaging material may be the following packaging container. It is sufficient that the methacrylic resin and the compound represented by general formula (1) are in contact with each other, and the compound represented by general formula (1) may be present inside the methacrylic resin, or the methacrylic resin and the compound represented by general formula (1) may be packaged in a dry blend state. It is preferable that the methacrylic resin and the compound represented by general formula (1) are dry blended.

[0044] [Package] Since the storage stability after dissolving in cyanoacrylate such as ethyl cyanoacrylate tends to deteriorate due to the effect of promoting anionic polymerization, the packaging material used for the package is required to be substantially impermeable to moisture and to be airtight. For example, metal containers or cans, films on which metal aluminum is vapor-deposited, polyethylene, etc. can be suitably used as such packaging materials. It is also preferable to dehumidify the inside of the packaging container by replacing it with dehumidified gas or by packing a moisture absorbent before packaging the pellet or bead-shaped methacrylic resin.

[0045] More specifically, the packaging container (packaging material) has a water vapor permeability of 1.0 g / (m 2 In one embodiment, the thickener for cyanoacrylate adhesives is preferably made of a material having a water vapor permeability of 1.0 g / (m 2 It is preferable that the package is sealed with a material that has a shelf life of less than 24 h. Examples of such materials include metal materials such as iron, copper, steel, thin steel-tin-plated material, and stainless steel with a thickness of 10 μm or more, polyvinylidene chloride-coated films using biaxially oriented polypropylene or polyethylene terephthalate films as substrates, aluminum vapor deposition films, silica vapor deposition films, and biaxially oriented polypropylene films with a thickness of 50 μm or more and containing an extremely low level of additives that may bleed out. By packaging the thickener of this embodiment in the packaging material as described above to form a package, the storage stability of the thickener can be further improved.

[0046] <Weight average molecular weight> The weight average molecular weight of the above-mentioned methacrylic resin was measured by gel permeation chromatography (GPC) when the weight average molecular weight of the methacrylic resin was 1,800,000 or less, and was measured by GPC-MALS when the weight average molecular weight of the methacrylic resin was more than 1,800,000.

[0047] The ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn of the methacrylic resin measured by gel permeation chromatography (GPC) is preferably 1.7 or more and 2.5 or less. From the viewpoint of ease of production, Mw / Mn is more preferably 1.8 or more. Furthermore, from the viewpoint of suppressing undissolved matter during dissolution and improving solubility, Mw / Mn is more preferably less than 2.5, even more preferably 2.4 or less, particularly preferably 2.3 or less, and particularly preferably less than 2.3.

[0048] The weight average molecular weight Mw and number average molecular weight Mn measured by the GPC are determined in advance by preparing a calibration curve from the elution time and weight average molecular weight using a standard methacrylic resin that is available as a reagent with a known monodisperse weight average molecular weight and an analytical gel column that is eluted from the high molecular weight component. The molecular weight of each sample can be measured from the calibration curve. Specifically, the molecular weight may be measured by the method described in the Examples below.

[0049] The ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn of the methacrylic resin measured by the GPC-MALS is preferably 1.0 or more and 3.0 or less. From the viewpoint of suppressing residuals when dissolving cyanoacrylate and improving solubility, Mw / Mn is more preferably 1.0 or more and less than 2.3.

[0050] <Moisture percentage> The moisture content of the methacrylic resin can be measured by the method described in the Examples below, and is measured by a drying method, in which 10.0 g of the methacrylic resin is kept at 70° C., and the measurement is terminated when the weight loss rate in 10 seconds becomes 0.02% or less, and the total weight loss rate is regarded as the moisture content.

[0051] The moisture content of the methacrylic resin (for example, methacrylic resin in the form of pellets or beads) can be adjusted, for example, by a drying method for the slurry after polymerization.

[0052] Methods for drying methacrylic resin include hot air drying, which involves blowing hot air into a tank from a hot air blower or blow heater, etc., vacuum drying, which involves drying by reducing the pressure inside the system and then heating it as necessary, barrel drying, which involves rotating the obtained polymer in a container to remove moisture, spin drying, which involves drying using centrifugal force, airflow drying, which involves transporting the resin in a pipe while drying it with hot air, and a fluidized bed dryer, in which the bottom of the tank opens and closes to drop the resin into the next drying tank after drying for a certain period of time at a specific temperature.

[0053] In order to make the moisture content fall within the above range, it is preferable to dry the obtained slurry after the polymerization is completed using a flash dryer and / or a fluidized bed dryer. In this case, if the final moisture content is significantly low, the processing time is long, resulting in poor productivity, and problems such as pump-up failure may occur in the slurry delivery step.

[0054] <Average particle size> The average particle size refers to the volume average particle size, which can be measured by the method described in the Examples below.

[0055] The thickener of the present embodiment is particularly used for cyanoacrylate adhesives. Here, the cyanoacrylate adhesive preferably contains an alkyl cyanoacrylate as a main component (for example, the mass ratio of alkyl cyanoacrylate is 50 mass% or more, more preferably 70 mass% or more, relative to 100 mass% of the adhesive).

[0056] Examples of the alkyl cyanoacrylate include cyanoacrylates having an alkyl group having 1 to 10 carbon atoms, such as methyl cyanoacrylate, ethyl cyanoacrylate, propyl cyanoacrylate, isopropyl cyanoacrylate, butyl cyanoacrylate, isobutyl cyanoacrylate, and octyl cyanoacrylate; methoxyethyl cyanoacrylate, and ethoxyethyl cyanoacrylate. Generally, ethyl cyanoacrylate is often used as the alkyl cyanoacrylate.

[0057] <Polymerization method> The methacrylic resin can be produced, for example, using a monomer constituting the methacrylic resin, a polymerization initiator, a chain transfer agent, and other additives.

[0058] As the polymerization initiator, when free radical polymerization is used, peroxide-based initiators such as di-t-butyl peroxide, lauryl peroxide, dilauroyl peroxide, t-butylperoxy 2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and azo-based initiators such as azobisisobutyronitrile, azobisisovaleronitrile, and 1,1-azobis(1-cyclohexanecarbonitrile) can be used, which can be used alone or in combination of two or more kinds. These radical initiators can be combined with a suitable reducing agent to be used as a redox-based initiator. In the case of suspension polymerization or emulsion polymerization, it is preferable to use a polymerization initiator having a 10-hour half-life temperature of less than 65° C. Specifically, dilauroyl peroxide is preferable.

[0059] The polymerization initiator is generally used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers.

[0060] In the method for producing a methacrylic resin, when the resin is produced by a radical polymerization method, a commonly used chain transfer agent can be used to adjust the molecular weight.

[0061] As the chain transfer agent, for example, mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tristhioglycolate, and pentaerythritol tetrakis(thioglycolate) are preferably used.

[0062] The chain transfer agent may be used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers. The amount of the chain transfer agent is determined depending on the desired molecular weight.

[0063] As a polymerization method for methacrylic resin, suspension polymerization or emulsion polymerization is preferably used in terms of small particle size. Since suspension polymerization gives particulate resin beads and emulsion polymerization gives powdery resin beads, it is advantageous in terms of operation when dissolving an appropriate amount as a thickener to adjust the syrup to the desired viscosity.

[0064] Furthermore, since the polymerization time of suspension polymerization is shorter than that of emulsion polymerization, suspension polymerization is preferred.

[0065] In particular, when using a suspension polymerization method, it is preferable to set the molecular weight distribution within the above-mentioned range, and when it is highly required to suppress the generation of unmelted matter due to the broadness of the molecular weight distribution when dissolving in cyanoalkyl acrylate or the like, and to maintain high storage stability after dissolution, it is preferable to obtain the product by one-stage suspension polymerization rather than multi-stage polymerization, which results in a broad molecular weight distribution. Two-stage polymerization is not preferable because it increases the amount of impurities derived from the suspending agent.

[0066] As a method for polymerizing the methacrylic resin, it is preferable to use a method in which a suspending agent having an average particle size of 10 to 40 μm is dispersed in water and polymerized. Among them, it is preferable to disperse a suspending agent having an average particle size of 10 to 40 μm in water and perform one-stage suspension polymerization.

[0067] In the method for producing methacrylic resin, it is preferable to carry out polymerization with the average particle size of the suspending agent dispersed in the suspension polymerization water set to 10 to 40 μm. This makes it possible to control the standard deviation of the volumetric particle size of the methacrylic resin (e.g., methacrylic resin beads), stabilize the polymerization behavior, reduce the amount of heat removal, and improve productivity.

[0068] The average particle size of the suspension can be adjusted by appropriately selecting the particle size of the suspension used. Furthermore, a suspension with an appropriate average particle size can be obtained by mixing powders with different particle sizes.

[0069] In the method for producing a methacrylic resin, it is preferable to adjust the pH of the aqueous phase to a range of 4 to 7. By adjusting the pH within this range, the standard deviation of the particle size of the beads can be controlled, and the polymerization behavior can be stabilized.

[0070] In the method for producing methacrylic resin, it is preferable to adjust the temperature of the suspending agent to 50°C to 90°C in advance and then add it to the water (50°C to 90°C) in the reactor. This makes it possible to adjust the average particle size of the methacrylic resin (e.g., methacrylic resin beads) and its variation.

[0071] Depending on the manufacturing method of the methacrylic resin, it is preferable to use an inorganic suspending agent rather than an organic suspending agent. This is because the residue of the organic suspending agent may make it difficult to adjust the viscosity of the cyanoacrylate adhesive. Here, examples of the organic suspending agent include polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, gelatin, polyvinyl acetate, etc.

[0072] Considering the stability after dissolution in alkyl cyanoacrylate, the inorganic suspending agent is preferably one containing an inorganic compound containing calcium and / or aluminum, and examples of the inorganic suspending agent include calcium phosphate such as tricalcium phosphate (calcium tertiary phosphate), calcium carbonate, aluminum hydroxide, etc. In particular, from the viewpoint of stability after dissolution, the inorganic suspending agent is more preferably one containing an inorganic compound containing aluminum.

[0073] The suspending agent may further contain a suspending aid such as polyethylene glycol, sodium ethylenediaminetetraacetate, sodium lauryl sulfate, etc. The suspending aid may be present in an amount of 0.01 to 10% by mass relative to 100% by mass of the suspending agent.

[0074] The suspending agent is preferably used by mixing it in water together with the monomer raw material.

[0075] <Cleaning method> In the method for producing a methacrylic resin, it is preferable to carry out operations such as acid washing, water washing, and alkali washing in order to remove the suspending agent. The number of times that these washing operations are carried out may be selected optimally from the viewpoints of work efficiency and suspending agent removal efficiency, and may be repeated once or multiple times.

[0076] The temperature at which the washing is carried out may be optimally selected in consideration of the efficiency of removing the suspending agent, the degree of coloration of the resulting polymer, etc., and is preferably 20 to 100° C. The temperature at which the washing is carried out is more preferably 30 to 95° C., further preferably 40 to 95° C., and particularly preferably 50 to 80° C.

[0077] The washing time per washing is preferably 10 to 180 minutes, more preferably 20 to 150 minutes, from the viewpoints of washing efficiency, reduction of odor when used as a thickener, and dissolution stability in cyanoacrylate.

[0078] The pH of the washing solution used in washing may be within a range that allows removal of the suspending agent, and is preferably pH 1 to 12. When performing acid washing, the pH is preferably pH 1 to 5, more preferably pH 1.2 to 4, from the viewpoint of the efficiency of removing the suspending agent and the color tone of the resulting polymer. The acid used in acid washing may be any acid that allows removal of the suspending agent, and is not particularly specified, but a conventionally known inorganic acid or organic acid may be used. Examples of the acid that can be suitably used include inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and boric acid, each of which may be used in a diluted solution diluted with water or the like. Examples of the organic acid include those having a carboxyl group, a sulfo group, a hydroxyl group, a thiol group, and an enol group. Considering the effect of removing the suspending agent and the color tone of the resulting resin, the acid used in acid washing is more preferably nitric acid, sulfuric acid, or an organic acid having a carboxyl group.

[0079] After the acid washing, it is preferable to further wash with water or wash with an alkali from the viewpoint of suppressing insoluble residues when dissolved in cyanoacrylate. More preferably, washing is performed with hot water of 50° C. or higher, and even more preferably, washing is performed with hot water of 50° C. or higher, and then washing with an alkali and / or hot water of 50° C. or higher is performed.

[0080] By adjusting the pH of the slurry after washing to 2 or more and 9 or less, preferably 4 or more and 7 or less, more preferably 5 or more and 6.8 or less, and particularly preferably 5.5 or more and 6.5 or less, a thickener that has excellent storage stability when dissolved in cyanoacrylate and also has excellent light resistance can be obtained.

[0081] [Additives] The thickener of the present embodiment may optionally contain other additives. The additives are not particularly limited as long as they can exert the effects of the present invention, and may be appropriately selected depending on the purpose.

[0082] Examples of additives include, but are not limited to, various stabilizers such as ultraviolet absorbers, heat stabilizers, and light stabilizers; plasticizers; flame retardants; flame retardant assistants; curing agents; curing accelerators; antistatic agents; conductivity imparting agents; stress relaxation agents; mold release agents; crystallization accelerators; hydrolysis inhibitors; lubricants; impact imparting agents; sliding property improvers; compatibilizers; nucleating agents; reinforcing agents; flow adjusters; dyes; sensitizers; colorants; anti-settling agents; anti-sagging agents; fillers; defoamers; light diffusing fine particles; rust inhibitors; antibacterial agents; anti-fungal agents; anti-fouling agents; conductive polymers, and the like.

[0083] The thickener of the present embodiment may be the methacrylic resin obtained by the above-mentioned method as it is, or may be mixed with other methacrylic resin compositions to form a thickener.

[0084] The thickener of the present embodiment can be suitably used in particular as a cyanoacrylate (preferably an alkyl cyanoacrylate, more preferably an ethyl cyanoacrylate)-based thickener.

[0085] The mass proportion of the methacrylic resin in the thickener is preferably 80 to 90 mass %, and more preferably 90 to 97 mass %, relative to 100 mass % of the thickener.

[0086] <pH of the aqueous phase when the thickener is dispersed in water> The thickener preferably has a pH of 2 to 9 in the supernatant aqueous phase, which is measured at room temperature after stirring and dispersing 20 g of the thickener in 100 g of pure water, leaving the thickener to stand, and allowing the solids to settle. In order to maintain a particularly good hue when the thickener is dissolved and used, to improve solubility in cyanoacrylate, and to suppress odors derived from residual substances, the pH of the supernatant aqueous phase is more preferably 3 or more, and particularly preferably 3.5 or more. In order to improve storage stability after dissolving in cyanoacrylate, etc., the pH of the supernatant aqueous phase is preferably 8.5 or less, more preferably 8 or less, and particularly preferably 7.5 or less.

[0087] <Water vapor permeability> The water vapor transmission rate is "the amount of water vapor that passes through a test piece of unit area in unit time under conditions of a temperature of 40° C. and a humidity of 90% RH" and is measured by the cup method described in JIS Z 0208.

[0088] [Cyanoacrylate adhesive] The present invention also discovers that by contacting a methacrylic resin with a compound represented by general formula (1) and then dissolving a thickener for cyanoacrylate adhesives in the cyanoacrylate adhesive, the storage stability of the cyanoacrylate adhesive is superior to that obtained when the methacrylic resin and the compound containing general formula (1) are added separately to the cyanoacrylate. That is, one embodiment of the present invention is a method for producing a cyanoacrylate adhesive, which comprises contacting a bead-shaped methacrylic resin having a moisture content of 1 mass % or less with a compound represented by general formula (1) in an amount of 0.01 mass % to 10 mass % relative to 100 mass % of the methacrylic resin, and then dissolving the compound in a cyanoacrylate adhesive. As described above, the cyanoacrylate adhesive produced by the above production method has better storage stability. The thickener of the present embodiment is preferably used in a cyanoacrylate adhesive. The cyanoacrylate adhesive preferably contains the thickener of the present embodiment and a cyanoacrylate (preferably an alkyl cyanoacrylate). The cyanoacrylate adhesive may further contain an additive.

[0089] The adhesive preferably has a viscosity ratio when stored at 70°C (viscosity at 25°C after standing at 70°C for 2 weeks / initial viscosity at 25°C) of 1.0 or more and less than 1.4. Here, this viscosity refers to a value measured with a vibration type viscometer, and can be measured by the method described in the examples below.

[0090] The above viscosity ratio is more preferably from 1.0 to 1.35, and even more preferably from 1.0 to 1.3. When the viscosity ratio is within this range, an adhesive having stable handleability can be obtained.

[0091] From the viewpoint of handling, the initial viscosity of the dissolved methacrylic resin at 25°C is desirably 0.5 to 2.0 Pa s. The specific concentration of the methacrylic resin is preferably 3 to 30 mass% dissolved in cyanoacrylate (preferably alkyl cyanoacrylate, more preferably ethyl cyanoacrylate) relative to 100 mass% of the adhesive, more preferably 4 to 25 mass%, and even more preferably 5 to 20 mass%.

[0092] The temperature at which the methacrylic resin is dissolved is preferably 30° C. or higher from the viewpoint of ease of dissolution, and is preferably 80° C. or lower from the viewpoint of stability. EXAMPLES

[0093] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples in any way.

[0094] <Raw materials for methacrylic resins B-1 to B-3> The raw materials used for producing the methacrylic resins B-1 to B-3 are as follows. Methyl methacrylate (MMA): Asahi Kasei (containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Butyl acrylate (BA): Toagosei (contains 15 ppm by mass of 4-methoxyphenol as a polymerization inhibitor) 2-Ethylhexyl thioglycolate (EHTG): Arkema Dilauryl peroxide (LPO): Made by Nippon Oil & Fats Tetrasodium ethylenediaminetetraacetate dihydrate (EDTA): Kishida Chemical Aluminum hydroxide: Nippon Light Metal Co., Ltd. SBX73, B303, B153, B103 (average particle size was adjusted by appropriately mixing each.)

[0095] [I. Production of methacrylic resin beads for use as thickener] Example 1 - Preparation of suspension - 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 33 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added to a vessel equipped with a stirrer equipped with four inclined paddle blades and mixed to obtain a mixed solution (a1). The average particle size of the suspension in the mixed solution (a1) was 33 μm, and the pH of the obtained mixed solution (a1) was 5.5. The obtained mixed solution (a1) was heated to 70°C.

[0096] -Polymerization reaction- Next, 25 kg of water was added to a 60L reactor and the temperature was raised to 80°C, and 3 kg of the mixed solution (a1) and a monomer solution having the composition shown in Table 1 below were added to the reactor. Then, the temperature was kept at about 80°C to carry out suspension polymerization, and a peak of heat generation was observed 180 minutes after the monomer solution was added. Then, the temperature was raised to 93°C at a rate of 1°C / min, and the temperature was kept at about 93°C for 45 minutes, and then the polymerization reaction was substantially terminated to obtain a polymer slurry. Next, the obtained polymer slurry was cooled to 50°C. 20% by mass sulfuric acid was added to the polymer slurry to dissolve the suspending agent, and a polymerization reaction solution was obtained. Next, the obtained polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, filtered, and separated into bead-like methacrylic resin particles and a suspension waste liquid. The pH of the suspension waste liquid was 3.3.

[0097] -Cleaning process- Thereafter, an amount of ion-exchanged water at about 70°C approximately equal to the amount of the bead-like methacrylic resin particles was added, followed by stirring, washing, and filtration. Thereafter, washing with ion-exchanged water at about 70°C was similarly carried out once more (a total of two water washes) to obtain a slurry polymer solution. Aqueous sodium hydroxide solution was added dropwise to the obtained slurry polymer solution to adjust the pH to 8.5, and the solution was stirred and washed. Thereafter, the slurry polymer solution was filtered, and further ion-exchanged water at 70°C was added, followed by stirring and washing. The pH of the obtained slurry polymer solution was 6.1. Thereafter, the slurry polymer solution was filtered to obtain resin beads. The obtained resin beads were dried in an airflow dryer at 150°C (30 Nm 3 / hr), then in a fluidized bed dryer (25 Nm 3 / hr at 90°C for 5 minutes to obtain methacrylic resin beads (B-1). The obtained methacrylic resin beads (B-1) had an MMA:BA ratio of 99.5:0.5 (mass ratio), a weight average molecular weight of 1,600,000, an average particle size of 171 μm, and a moisture content of 0.2 mass%. Powdered 4-methoxyphenol (C-1) (trade name: MQ, solid (powder) at room temperature) (compound represented by general formula (1)) manufactured by Kawaguchi Chemical Industry Co., Ltd. was mixed into the obtained methacrylic resin beads in the amount shown in Table 2 below to serve as a thickener, and the beads were packaged together. The package was made of a packaging material containing aluminum (water vapor permeability: 0.8 g / (m 2 / 24h) and sealed with heat seal.

[0098] (Examples 2 to 4, Comparative Example 2) The same procedure as in Example 1 was repeated except that the amount of powdered 4-methoxyphenol (shown in Table 2 or Table 3 below) was changed.

[0099] Comparative Example 1 The same procedure as in Example 1 was carried out, except that powdered 4-methoxyphenol was not added.

[0100] Comparative Example 3 The procedure was the same as in Comparative Example 2, except that the methacrylic resin beads and powdered 4-methoxyphenol were not packaged together.

[0101] (Reference examples 1~4) The procedure was the same as in Examples 1 to 4, except that the methacrylic resin beads and powdered 4-methoxyphenol were not packaged together.

[0102] (Examples 5 to 9) The procedure was the same as in Example 2, except that instead of powdered 4-methoxyphenol (C-1), other compounds represented by general formula (1) (C-2 to C-6 shown below) were used. C-2: 4-Methoxyphenol (Tokyo Chemical Industry Co., Ltd., solid at room temperature) C-3: Hydroquinone (Tokyo Chemical Industry Co., Ltd., solid at room temperature) C-4: 6-tert-butyl-2,4-xylenol (Tokyo Chemical Industry Co., Ltd., liquid at room temperature) C-5: tert-butylhydroquinone (Tokyo Chemical Industry Co., Ltd., solid at room temperature) C-6: 4-tert-butylpyrocatechol (Tokyo Chemical Industry Co., Ltd., solid at room temperature)

[0103] (Examples 10 and 11) The monomer solution was prepared in the same manner as in Example 2, except that it was prepared as methacrylic resin (B-2) or (B-3) and had the composition shown in Table 1 below. The methacrylic resin (B-2) had a MMA:BA ratio of 99.5:0.5 (mass ratio), a weight average molecular weight of 450,000, an average particle size of 350 μm, and a moisture content of 0.2 mass%. The methacrylic resin (B-3) had a MMA:BA ratio of 99.5:0.5 (mass ratio), a weight average molecular weight of 4,600,000, an average particle size of 280 μm, and a moisture content of 0.2 mass%.

[0104] [Table 1]

[0105] (Reference examples 5~8) The same procedures were carried out as in Examples 5, 6, 8 and 9, except that the methacrylic resin beads and the other compound represented by general formula (1) were not packaged together.

[0106] Comparative Example 4 Reference Examples 5 to 8 were repeated except that C-7 (manufactured by Tokyo Chemical Industry Co., Ltd., 2,6-di-tert-butylphenol, solid at room temperature) was used instead of the compounds (C-2 to C-5) represented by general formula (1).

[0107] Comparative Example 5 The same procedure as in Comparative Example 4 was followed except that the methacrylic resin beads and C-7 were packaged together.

[0108] Comparative Example 6 The same procedure as in Comparative Example 5 was repeated, except that C-8 (manufactured by Tokyo Chemical Industry Co., Ltd., 2,6-di-tert-butyl-p-cresol, solid at room temperature) was used instead of C-7.

[0109] (Reference example 9) The same procedure as in Example 10 was followed except that C-1 (powdered 4-methoxyphenol) was not packaged together with the product in the same package.

[0110] [II. Physical properties of methacrylic resin] (II-1)(Weight average molecular weight) The weight average molecular weight of the obtained methacrylic resin beads B-1 and B-2 was measured using the following device and conditions. Measurement device: gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation. Column: one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series in this order. In this column, high molecular weight compounds elute early, while low molecular weight compounds elute late. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: Tetrahydrofuran, flow rate 0.6 mL / min 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse peak top molecular weights and different molecular weights were used. Peak top molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin. The weight average molecular weight (Mw) of the methacrylic resin was determined based on the area in the GPC elution curve and a calibration curve of a third-order approximation equation.

[0111] The weight average molecular weight of the methacrylic resin beads B-3 was measured using the following apparatus and conditions since the molecular weight was too high to be measured by the above method. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Columns: One TSKguardcolumn HXL-H and two TSKgel GMHXL were used. MALS:DAWN HELEOS II MALS laser wavelength: 659 nm Eluent: THF (Kishida Chemical Co., Ltd., Grade 1) Detection sensitivity: 3.0mV / min Column temperature: 40℃ RI detector temperature: 40℃ MALS temperature: room temperature Sample concentration: 0.5mg / mL Injection volume: 100μL

[0112] (II-2)(Moisture content) Using a SHIMADZU MOISTURE BALANCE MOC-120H, 10.0 g of methacrylic resin beads were held at 70° C., and the measurement was terminated when the weight loss rate over 10 seconds became 0.02% or less, and the total weight loss rate was taken as the moisture content.

[0113] (II-3)(Average particle size) The average particle size was measured using the laser scattering method of a Beckman Coulter LS13320 to measure the volume average particle size (μm) of methacrylic resin beads.

[0114] III. Evaluation of thickeners (III-1) (Storage stability at 70℃ for 2 weeks) As shown in the upper part of Fig. 1, in Examples 1 to 11 and Comparative Examples 2, 5, and 6, which were packaged together, the methacrylic resin and the compound represented by general formula (1) were placed in a packaging container, left in the packaged state at 50°C for one week, and then returned to room temperature to remove the thickener. The thickener was then placed in a 30 mL screw bottle together with cyanoacrylate adhesive A (manufactured by Alteco, product name "EE", viscosity: 3 mPa s), and shaken at 60°C for 2 hours in a thermostatic shaker (manufactured by Taitec Co., Ltd., BR-23UM) to dissolve, which was used as a sample. Then, a storage stability test was performed using the sample by the following method.

[0115] In Comparative Example 1, the methacrylic resin alone was left in its packaged state at 50°C for one week, then the temperature was returned to room temperature and the methacrylic resin was removed. This was then placed in a 30 mL screw bottle together with cyanoacrylate adhesive A (manufactured by Alteco, product name "EE", viscosity: 3 mPa s) and shaken at 60°C for 2 hours in a thermostatic shaker (BR-23UM made by Taitec Co., Ltd.) until it was dissolved, and this was used as the sample.

[0116] As shown in the lower part of Fig. 1, in Comparative Examples 3-4 and Reference Examples 1-9 in which the methacrylic resin was added separately, only the methacrylic resin was placed in a packaging container, and left at 50°C for one week with only the methacrylic resin packed in the container, and then the temperature was returned to room temperature to remove the methacrylic resin, which was then placed in a 30mL screw bottle together with cyanoacrylate adhesive A (manufactured by Alteco, trade name "EE", viscosity: 3mPa s) and compound C (compound represented by general formula 1), and shaken at 60°C for 2 hours in a thermostatic shaker (BR-23UM manufactured by Taitec Co., Ltd.) to dissolve the resin, which was used as a sample. Then, a storage stability test was performed using the sample by the following method.

[0117] The viscosity η1 of the sample at 25° C. was measured using a vibration viscometer VM-10A manufactured by Sekonic Corporation. The screw bottle was left in a sealed state in an oven at 70° C. for two weeks, after which the screw bottle was removed from the oven and the viscosity η2 of the sample at 25° C. was measured. The viscosity ratio η2 / η1 after storage at 70° C. for two weeks was defined as storage stability.

[0118] The storage stability after storage at 70°C for 2 weeks was evaluated as follows. Viscosity ratio η2 / η1 less than 1.3: A (very good) Viscosity ratio η2 / η1 is 1.3 or more and less than 1.35...B (good) Viscosity ratio η2 / η1 is 1.35 or more and less than 1.4...C (no problem) Viscosity ratio η2 / η1 is 1.4 or more...D (bad)

[0119] (III-2) (Storage stability when added separately - Storage stability when packaged together) The difference in the 70°C, 2-week storage viscosity ratio of the methacrylic resin B and the compound C represented by the general formula (1) in the same package and in the non-co-packaged state (added separately) was calculated from the values ​​shown in the corresponding Examples, Reference Examples, or Comparative Examples using the following formula. (Viscosity ratio when added separately) - (Viscosity ratio when packaged together) The values ​​in each example were calculated as follows. Example 1: (Viscosity ratio of Reference Example 1) - (Viscosity ratio of Example 1) Example 2: (Viscosity ratio of Reference Example 2) - (Viscosity ratio of Example 2) Example 3: (Viscosity ratio of Reference Example 3) - (Viscosity ratio of Example 3) Example 4: (Viscosity ratio of Reference Example 4) - (Viscosity ratio of Example 4) Example 5: (Viscosity ratio of Reference Example 5) - (Viscosity ratio of Example 5) Example 6: (Viscosity ratio of Reference Example 6) - (Viscosity ratio of Example 6) Example 8: (Viscosity ratio of Reference Example 7) - (Viscosity ratio of Example 8) Example 9: (Viscosity ratio of Reference Example 8) - (Viscosity ratio of Example 9) For example, since Example 1 and Reference Example 1 differ only in their packaging state, (viscosity ratio of Reference Example 1)-(viscosity ratio of Example 1) is a positive number, which indicates the effect of identical packaging.

[0120] [Table 2]

[0121] [Table 3]

[0122] From Tables 2 and 3, it can be seen that Examples 1 to 11, which are bead-shaped with an average particle size of 50 to 500 μm and contain a methacrylic resin with a moisture content of 1 mass% or less and a compound represented by the following general formula (1), have a relatively small viscosity ratio, and therefore show little viscosity change and excellent storage stability. In addition, by comparing the storage stability when packaged together with that when added separately, it can be seen that packaging together is effective. [Industrial Applicability]

[0123] According to the present invention, it is possible to provide a thickener that has excellent storage stability when used as a thickener for cyanoacrylate adhesives.

Claims

1. A bead-shaped methacrylic resin having an average particle size of 50 to 500 μm and a moisture content of 1% by mass or less; A compound represented by the following general formula (1): A thickener for cyanoacrylate adhesives, comprising 0.01% by mass to 10% by mass of a compound represented by the general formula (1) relative to 100% by mass of a methacrylic resin. 【Chemistry 1】 [In general formula (1), R 1 represents a hydrogen atom, a methyl group, or a tertiary butyl group; R 2 , R 3 each independently represents a hydrogen atom, a methyl group, a tertiary butyl group, a hydroxyl group, or a methoxy group. 1 , R 2 and R 3 The total number of tertiary butyl groups is less than 2.

2. 2. The thickener for cyanoacrylate adhesives according to claim 1, wherein the weight average molecular weight of the methacrylic resin is 85,000 or more and 5,000,000 or less.

3. 2. The thickener for cyanoacrylate adhesives according to claim 1, wherein the compound represented by the general formula (1) is in the form of powder at room temperature.

4. 2. The thickener for cyanoacrylate adhesives according to claim 1, wherein the compound represented by the general formula (1) contains two hydroxyl groups or one hydroxyl group and one methoxy group.

5. A method for producing the cyanoacrylate adhesive thickener according to claim 1, comprising the steps of: A drying step of volatilizing water from the methacrylic resin; and a packaging step of packaging the methacrylic resin and the compound represented by general formula (1) in a packaging material after the drying step.

6. The thickener for cyanoacrylate adhesives according to claim 1 is used in a composition having a water vapor permeability of 1.0 g / (m 2 - A packaged body sealed with packaging material for less than 24 hours.

7. A method for producing a cyanoacrylate adhesive, comprising contacting a bead-shaped methacrylic resin having an average particle size of 50 to 500 μm and a moisture content of 1 mass % or less with a compound represented by the following general formula (1) in an amount of 0.01 mass % to 10 mass % relative to 100 mass % of the methacrylic resin, and then dissolving the compound in a cyanoacrylate adhesive. 【Chemistry 2】 [In general formula (1), R 1 represents a hydrogen atom, a methyl group, or a tertiary butyl group; R 2 , R 3 each independently represents a hydrogen atom, a methyl group, a tertiary butyl group, a hydroxyl group, or a methoxy group. 1 , R 2 and R 3 The total number of tertiary butyl groups is less than 2.

Citation Information

Patent Citations

  • Pyrrole dye with excellent spectral absorption characteristic

    JP1992015267A

  • Resin composition, thickener

    JP2018178076A

  • α-Cyanoacrylate adhesive composition

    JP3018859B2